2022
DOI: 10.4317/medoral.25164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a local single dose administration of growth hormone on the osseointegration of titanium implants

Abstract: Background The aim of the present study was to evaluate the effect of different concentrations of growth hormone (GH) on endosteal implant’s surface at the early stages of osseointegration. Material and Methods Sixty tapered acid-etched titanium implants were divided into four groups: i) Collagen, used as a control group; and three experimental groups, where after collagen coating, GH was administered directly to the surface in varying concentrations: ii) 0.265 mg, iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For instance, previous pre-clinical research in sheep presented the application of different doses of growth hormone and parathyroid hormone applied directly to the implant surface prior installation in low-density bone. Interestingly, both studies presented no significant differences in BIC and BAFO [ 46 , 47 ]. In a previous in vitro drug release profile study, it was reported the use of a thermo-sensitive hydrogel composite drug delivery system for the administration of DIPY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous pre-clinical research in sheep presented the application of different doses of growth hormone and parathyroid hormone applied directly to the implant surface prior installation in low-density bone. Interestingly, both studies presented no significant differences in BIC and BAFO [ 46 , 47 ]. In a previous in vitro drug release profile study, it was reported the use of a thermo-sensitive hydrogel composite drug delivery system for the administration of DIPY.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature evaluating local and sustained drug release at the bone–implant interface in different animal models revealed a positive influence of locally delivered chemical compounds during the osseointegration process [ 32 ]. While several chemical substances have been reported in previous pre-clinical trials aiming to hasten the osseointegration process in low density/quality bone (calcium phosphate, bisphosphonates, growth factors such as BMPs and hormones such as growth hormone and parathyroid hormone) [ 32 , 46 , 47 ], the ideal adjunctive osteogenic therapy to accelerate bone formation around titanium implants in challenging scenarios remains unclear. To the best of the authors’ knowledge, this is the first study to report the association of the osteoinductive properties of DIPY with endosteal titanium implants in an effort to facilitate the osseointegration process in inferior, low-density bone.…”
Section: Introductionmentioning
confidence: 99%